Inequality, Social Protests and Civil War (2017)
The following article presents a series of hypotheses to analyze the possible transitions between protest and civil war and their relation to inequality. To do so, the article presents an analysis on the emergence of protests and its relation with the increase in inequality across the world. This increase in inequality can in fact lead to social unrest, instability and in some cases facilitate the emergence of future armed conflicts. Thus this scenario of increased inequality presents different possible trajectories: 1) protest generated by inequality can escalate into civil conflicts and civil war, or 2) protest generated by inequality can facilitate processes of participation and democratic consolidation. The possibility of either of these transitions taking place is defined by the structural conditions that define the interactions between protestors and authorities in particular settings.